EFFECT OF AIR POLLUTION ON DETERMINATION OF THRESHOLD TEMPERATURES FOR HEAT AND COLD WAVES IN SPAIN. - J.A. López-Bueno; J. Díaz; M.A. Navas-Martín; G. Sánchez-Martínez; P. Salvador; C. Linares (Environmental Pollution, 2026)

Valid and Reliable Questionnaire for Assessing Nutrition and Physical Activity Practices in Early Care and Education - Christina M. Becker; Janice Kao; Sridharshi C. Hewawitharana; Carolyn D. Rider; Amanda Linares; Ron Strochlic; Miranda Westfall Brown; Gail Woodward-Lopez (Journal of Nutrition Education and Behavior, 2026)

Different strategies to obtain laccase-based time-temperature indicator for monitoring of cold chain storage and management - Camila Regina Hackenhaar; Vinicius Zimmermann; Lucas dos Santos Linares; Victor Moreira Cannavon; Juan M. Bolivar; Roberto Fernandez-Lafuente; Rafael C. Rodrigues (Innovative Food Science & Emerging Technologies, 2026)

Analysis and removal of matrine in liquorice raw materials by good manufacturing practices - Maria C. Millan-Linares; Maria E. Martin (Food and Humanity, 2026)

Controls on the distribution of 7Be for an improved understanding of sediment and associated contaminant storage - Enrique G. Muñoz-Arcos; Caroline C. Clason; Geoffrey E. Millward; Claudio M. Bravo-Linares; Robert Clough; William H. Blake (Journal of Soils and Sediments, 2026)

How does geographical scale affect the effectiveness of public health heat-wave prevention plans?: the case of Spain - C. Linares; J. A. López-Bueno; M. A. Navas; M. S. Ascaso; S. González; Julio Díaz (International Journal of Biometeorology, 2026)
The summer of 2025 has been the hottest in Spain since records began, 2022registering temperatures one tenth of a degree Celsius higher than the hottest on record to date, i.e., the summer of 2022. However, mortality attributable to heat wave temperatures in 2025 was 908 deaths fewer than in 2022. Of the many factors that may have influenced the reduction in attributable mortality in 2025 with respect to 2022, this study sought to analyse the possible impact of an improvement made to heat-wave prevention plans in the form of enhancing the geographical resolution of health alerts. Using the annual heat wave intensity registered and the annual mortality attributable to these heat waves, a linear adjustment between these two variables was performed for all Spanish provinces in the above two periods. The results indicated that whereas the increase in annual mortality for every one-degree rise in annual heat wave intensity (mean slope of the lines of fit for Spain as a whole) from 2015 to 2023 was 1.74 deaths/⁰C, in the period 2024–2025 it was 1.66 deaths/⁰C. This result translates as follows: if annual attributable mortality in Spain were calculated for 2025 using the values of the slopes for the first period, this would yield a total of 4,082 attributable deaths, but if this same attributable mortality were calculated using the values of the slope corresponding to the 2024–2025 period, this would yield a total of 3,894 deaths. In conclusion, although this analysis has not taken into account many factors that could relate heat wave intensity to temperature-attributable mortality, the activation of heat wave thresholds in prevention plans at a smaller geographical scale could lead to a reduction in attributable mortality.

How air pollution and extreme temperatures affect emergency hospital admissions due to neurological diseases: A study in 10 Spanish provinces - M. Iriso; C. Linares; J. Díaz; R. Ruiz-Páez; M.A. Navas; J. López-Bueno (Atmospheric Environment, 2026)

Elucidation of xenobiotics in textiles for infants using non-targeted approaches: The role of fabrics as a source of early-life exposure to potentially harmful chemicals - A. Domínguez-Liste; E. Linares-Ruiz; M.O. Schweiss; L. Papay-Ramírez; C. Freire; P. Pérez-Serrano; R. Quesada-Jiménez; F.M. Pérez-Carrascosa; V. Mustieles; J.P. Arrebola; J. Pérez-del-Palacio; O. Ballesteros; et al. (Environmental Research, 2025)

High‐resolution coral oxygen and carbon isotope records reveal temperature and autotrophy dynamics in a Mediterranean climate change hotspot - Diego K. Kersting; Thomas C. Brachert; Juan P. D'Olivo; Cristina Linares; Lars Reuning; Joan Lluís Riera; Philipp Spreter; Ulrich Struck; Marina J. Vergotti; Jens Zinke (Limnology and Oceanography, 2025)
The Mediterranean Sea is warming at a rate exceeding the global average. Long‐term, high‐resolution data are essential for contextualizing changes within broader temporal scales, and coral skeletons provide valuable environmental archives, especially in data‐sparse regions or as supplements to existing records. While coral‐based reconstructions are well established in tropical settings, they remain limited in temperate areas. As the only reef‐building zooxanthellate coral in the Mediterranean, Cladocora caespitosa is particularly important for expanding coral‐based environmental archives in these understudied regions. Here, we present records of δ 18 O and δ 13 C in the skeletons of C. caespitosa from a global change sentinel site in NW Mediterranean. This study provides the most accurate temperature–δ 18 O calibration equations for C. caespitosa , including a traditional linear model and a novel exponential model that better accounts for the region's wide seasonal temperature range. Both calibrations rely on long‐term in situ water temperature data and a multi‐corallite composite approach to reduce non‐climatic variability. Seasonal trends in δ 13 C reveal, for the first time, variation in the coral's autotrophy–heterotrophy balance, while geochemical anomalies in the skeletons signal thermal stress effects on biomineralization. Our findings establish C. caespitosa skeletons as critical archives for reconstructing anthropogenic warming and its ecological effects in the Mediterranean.

Short-term effects of chemical and noise pollution during heat and cold waves on emergency hospital admissions in Madrid - R Ruiz-Páez; JA López-Bueno; J Díaz; MA Navas; C. Linares (International Journal of Biometeorology, 2025)
Cold and heatwaves and air pollution have a joint, direct impact on population health. The aim of this study was to evaluate the combined impact of chemical air and noise pollution on hospital admissions during warm and cold months, with a breakdown by age group. We conducted a time-series study of unscheduled emergency admissions by specific causes in Madrid across the period 2013–2018. The independent variables were daily mean concentrations of PM 2.5 , PM 10 , NO 2 , tropospheric ozone, noise, and maximum and minimum temperatures. Relative and attributable risks were calculated using generalised linear models with a Poisson link. During the warm months, stronger associations were found between: ozone and admissions due to respiratory, circulatory and neurological causes; NO 2 and admissions due to respiratory diseases; and PM and admissions due to dementia and Alzheimer’s disease. Heat had a greater effect on admissions due to neurological diseases. During the cold months, no association was found with any chemical air pollutant, except for NO 2 and asthma-related admissions. By age, the greatest impacts were registered for PM, noise, cold and heat at ages ≥ 65 years, and for noise, NO 2 and cold at ages ≤ 14 years.

How air pollution affects cause-specific emergency hospital admissions on days with biomass combustion in Spain? - E. Botezat; C. Linares; P. Salvador; M.A. Navas; J. Díaz; J.A. López-Bueno (Science of The Total Environment, 2025)

How air pollution and extreme temperatures affect emergency hospital admissions due to various respiratory causes in Spain, by age group: A nationwide study - C. Linares; J. Díaz; M.A. Navas; R. Ruiz-Páez; M. Saez; M.A. Barceló; J.A. López-Bueno (International Journal of Hygiene and Environmental Health, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Impact of Amaranthus spp. weed presence on the population abundance of Spodoptera cosmioides (Lepidoptera: Noctuidae) in genetically engineered soybean crops - Jorge G. Hill; Paula G. Páez Jerez; Patricia C. Fernández; Facundo Herrera Linares; M Florencia Rocha; M Teresa Vera (Crop Protection, 2025)

Quantifying bycatch of cold-water gorgonians to propose a dynamic management strategy for sustainable artisanal fishing on the mediterranean continental shelf - M. Montseny; C. Linares; N. Viladrich; J.L.L. Riera; M. Biel-Cabanelas; P. Baena; E. Quintanilla; S. Ambroso; J. Grinyó; A. Santín; J. Salazar; J.M. Gili; et al. (Ocean & Coastal Management, 2025)

Does the new European Union air quality directive really protect health? A nationwide case study in Spain - C. Linares; J. Díaz; M.A. Navas; J.A. López-Bueno (Science of The Total Environment, 2025)

Economic estimation and impact of air pollution and temperature extremes on emergency hospital admissions in Spain - R. Ruiz-Páez; J. Díaz; J.A. López-Bueno; M. Saez; M.A. Barceló; M.A. Navas; C. Linares (Science of The Total Environment, 2025)

The impacts of alien species on river bioassessment - Maria João Feio; Janine P. da Silva; Robert M. Hughes; Francisca C. Aguiar; Carlos B.M. Alves; Sebastian Birk; Marcos Callisto; Marden S. Linares; Diego R. Macedo; Paulo S. Pompeu; Wayne Robinson; Christian Schürings; et al. (Journal of Environmental Management, 2025)

Fine sediment-associated contaminants in gravel bed rivers: Evaluating storage times and turnover using fallout radionuclides (FRNs) - Enrique G. Muñoz-Arcos; Geoffrey E. Millward; Caroline C. Clason; Claudio M. Bravo-Linares; William H. Blake (Science of The Total Environment, 2025)

Variability of fallout radionuclides (FRNs) in river channels: implications for sediment tracing - Enrique Muñoz-Arcos; Geoffrey E. Millward; Caroline C. Clason; Richard Hartley; Claudio Bravo-Linares; William H. Blake (Journal of Soils and Sediments, 2024)

Short-term effects of fine particulate matter from biomass combustion and Saharan dust intrusions on emergency hospital admissions due to mental and behavioural disorders, anxiety and depression in Spain - R. Ruiz-Páez; J.A. López-Bueno; A. Padrón-Monedero; M.A. Navas; P. Salvador; C. Linares; J. Díaz (Science of The Total Environment, 2024)

How heatwaves affect short-term emergency hospital admissions due to bacterial foodborne diseases - M.S. Ascaso; J. Díaz; J.A. López-Bueno; M.A. Navas; I.J. Mirón; C. Linares (Science of The Total Environment, 2024)

In vivo evidences of the health-promoting properties of bioactive compounds obtained from olive by-products and their use as food ingredient - Fernando Rivero-Pino; Maria C. Millan-Linares; Alvaro Villanueva-Lazo; África Fernandez-Prior; Sergio Montserrat-de-la-Paz (Critical Reviews in Food Science and Nutrition, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Short-term impact of air pollution, noise and temperature on emergency hospital admissions in Madrid (Spain) due to liver and gallbladder diseases - J.A. López-Bueno; A. Padrón- Monedero; J. Díaz; M.A. Navas-Martín; C. Linares (Environmental Research, 2024)

Cadaveric study of the ultrasound-guided erector spinae plane block over the transverse process of the twelfth thoracic vertebra in dogs: Transversal vs longitudinal approach - M.E. Herrera-Linares; B. Rico-Pérez; D. Yaffy; R. Fernández-Parra; C. Llanos; C. Parra-Martínez; M.E. Herrera-Gutiérrez; S. Sanchis-Mora (The Veterinary Journal, 2024)

Denim washing wastewater treatment by coupling coagulation–flocculation/Fe-garnet filtration: life cycle assessment and the fertilization with the sludge - Y. Robles-Bueno; L. A. Castillo-Suárez; I. Linares-Hernández; V. Martínez-Miranda; L. Garduño-Pineda; C. Alanis; R. Natividad (International Journal of Environmental Science and Technology, 2024)

Identification, characterization, and molecular docking of immunomodulatory oligopeptides from bioavailable hempseed protein hydrolysates - Maria C. Millan-Linares; Fernando Rivero-Pino; Teresa Gonzalez-de la Rosa; Alvaro Villanueva; Sergio Montserrat-de la Paz (Food Research International, 2024)

Short-term impact of extreme temperatures, relative humidity and air pollution on emergency hospital admissions due to kidney disease and kidney-related conditions in the Greater Madrid area (Spain) - J.A. López-Bueno; J. Díaz; A. Padrón-Monedero; M.A. Navas Martín; C. Linares (Science of The Total Environment, 2023)

Production and identification of immunomodulatory peptides in intestine cells obtained from hemp industrial by-products - Sergio Montserrat-de la Paz; Alvaro Villanueva-Lazo; Francisco Millan; Victoria Martin-Santiago; Fernando Rivero-Pino; Maria C. Millan-Linares (Food Research International, 2023)

Venezuelan red mud: an environmental passive with catalytic applications in the reaction of thiophene hydrodesulfurization - M. Granados; J. Morancie; F. Ocanto; E. Figueredo; V.-C. Mujica; J. Marcano; C. F. Linares (International Journal of Environmental Science and Technology, 2023)

Impact of urban heat islands on morbidity and mortality in heat waves: Observational time series analysis of Spain's five cities - T. Cuerdo-Vilches; J. Díaz; J.A. López-Bueno; M.Y. Luna; M.A. Navas; I.J. Mirón; C. Linares (Science of The Total Environment, 2023)

Nutritional composition and biological activity of narrow-leafed lupins (Lupinus angustifolius L.) hydrolysates and seeds - Ana Lemus-Conejo; Fernando Rivero-Pino; Sergio Montserrat-de la Paz; Maria C. Millan-Linares (Food Chemistry, 2023)

Strengths and limitations of in silico tools to assess physicochemical properties, bioactivity, and bioavailability of food-derived peptides - Fernando Rivero-Pino; Maria C. Millan-Linares; Sergio Montserrat-de-la-Paz (Trends in Food Science & Technology, 2023)

Delineating vulnerability to drought using a process-based growth model in Pyrenean silver fir forests - Cristina Valeriano; Jan Tumajer; Antonio Gazol; Ester González de Andrés; Raúl Sánchez-Salguero; Michele Colangelo; Juan C. Linares; Teresa Valor; Gabriel Sangüesa-Barreda; J. Julio Camarero (Forest Ecology and Management, 2023)

Short-term effects of tropospheric ozone and other environmental factors on emergency admissions due to pregnancy complications: A time-series analysis in the Madrid Region - A. Calle-Martínez; R. Ruiz-Páez; L. Gómez-González; A. Egea-Ferrer; J.A. López-Bueno; J. Díaz; C. Asensio; M.A. Navas; C. Linares (Environmental Research, 2023)

Treatment processes and analysis of rainwater quality for human use and consumption regulations, treatment systems and quality of rainwater - C Morales-Figueroa; L A Castillo-Suárez; I Linares-Hernández; V Martínez-Miranda; E A Teutli-Sequeira (International Journal of Environmental Science and Technology, 2023)

How heat waves, ozone and sunlight hours affect endocrine and metabolic diseases emergency admissions? A case study in the region of Madrid (Spain) - A. Egea; C. Linares; J. Díaz; L. Gómez; A. Calle; M.A. Navas; R. Ruiz-Páez; C. Asensio; A. Padrón-Monedero; J.A. López-Bueno (Environmental Research, 2023)

The endangered coral Cladocora caespitosa in the Menorca Biosphere Reserve: Distribution, demographic traits and threats - D.K. Kersting; M.E. Cefalì; J. Movilla; M.J. Vergotti; C. Linares (Ocean & Coastal Management, 2023)

Nutritional composition, ultrastructural characterization, and peptidome profile of antioxidant hemp protein hydrolysates - Sergio Montserrat-de la Paz; Fernando Rivero-Pino; Alvaro Villanueva; Rocio Toscano-Sanchez; Maria E. Martin; Francisco Millan; Maria C. Millan-Linares (Food Bioscience, 2023)

Antimicrobial plant-derived peptides obtained by enzymatic hydrolysis and fermentation as components to improve current food systems - Fernando Rivero-Pino; Maria J. Leon; Maria C. Millan-Linares; Sergio Montserrat-de la Paz (Trends in Food Science & Technology, 2023)

Short-term impact of noise, other air pollutants and meteorological factors on emergency hospital mental health admissions in the Madrid region - L. Gómez González; C. Linares; J. Díaz; A. Egea; A. Calle-Martínez; M.Y. Luna; M.A. Navas; M.S. Ascaso-Sánchez; R. Ruiz-Páez; C. Asensio; A. Padrón-Monedero; J.A. López-Bueno (Environmental Research, 2023)

Air pollution and meteorological variables’ effects on COVID-19 first and second waves in Spain - J. Bañuelos Gimeno; A. Blanco; J. Díaz; C. Linares; J. A. López; M. A. Navas; G. Sánchez-Martínez; Y. Luna; B. Hervella; F. Belda; D. R. Culqui (International Journal of Environmental Science and Technology, 2023)

Short–term effects of air pollution and noise on emergency hospital admissions in Madrid and economic assessment - R. Ruiz-Páez; J. Díaz; J.A. López-Bueno; C. Asensio; M.S. Ascaso; M. Saez; M.Y. Luna; M.A. Barceló; M.A. Navas; C. Linares (Environmental Research, 2023)

Does the meteorological origin of heat waves influence their impact on health? A 6-year morbidity and mortality study in Madrid (Spain) - R. Ruiz-Páez; J. Díaz; J.A. López-Bueno; M.A. Navas; I.J. Mirón; G.S. Martínez; M.Y. Luna; C. Linares (Science of The Total Environment, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

FishShapes v1: Functionally relevant measurements of teleost shape and size on three dimensions - Samantha A. Price; Sarah T. Friedman; Katherine A. Corn; Olivier Larouche; Kasey Brockelsby; Anna J. Lee; Maya Nagaraj; Nick G. Bertrand; Mailee Danao; Megan C. Coyne; John R. Estrada; Rachel Friedman; et al. (Ecology, 2022)
Teleost fishes account for 96% of all fish species and exhibit a spectacular variety of body forms. Teleost lineages range from deep bodied to elongate (e.g., eels, needlefish), laterally compressed (e.g., ribbonfish) to globular (e.g., pufferfish), and include uniquely shaped lineages such as seahorses, flatfishes, and ocean sunfishes. Adaptive body shape convergence within fishes has long been hypothesized but the nature of the relationships between fish form and ecological and environmental variables remain largely unknown at the macroevolutionary scale. To facilitate the investigation of the interacting factors influencing teleost body shape evolution we measured eight functionally relevant linear traits on adult‐sized specimens along with specimen mass. Linear measurements of standard length, maximum body depth, maximum fish width, lower jaw length, mouth width, head depth, minimum caudal peduncle depth, and minimum caudal peduncle width were taken in millimeters with calipers, or tape measures for oversized specimens. We measured these traits on a total of 16,523 specimens (1–3 specimens per species) at the Smithsonian National Museum of Natural History and took approximately 7000 person hours of data collection to complete. The data went through a three‐step error‐checking process to clean and validate the data and then species averages were calculated. We present the complete specimen data set, which encompasses approximately one‐fifth of extant teleost species diversity, spanning ~90% of teleost families and ~96% of orders. The species and family names are compatible with the taxonomy used by FishBase and the order information with the phylogenetically informed taxonomy of Betancur‐R and colleagues published in 2014. This dataset is licensed under Creative Commons CC0 1.0 Universal (CC0 1.0) but please cite this paper when using the data or a subset of it.

Correction to: A study on correlations between precipitation ETCCDI and airborne pollen/fungal spore parameters in the NE Iberian Peninsula - R. Rodríguez-Solà; M. C. Casas-Castillo; J. J. Ho Zhang; R. Kirchner; M. Alarcón; C. Periago; C. De Linares; J. Belmonte (International Journal of Biometeorology, 2022)

A study on correlations between precipitation ETCCDI and airborne pollen/fungal spore parameters in the NE Iberian Peninsula - R. Rodríguez-Solà; M. C. Casas-Castillo; J. J. Ho Zhang; R. Kirchner; M. Alarcón; C. Periago; C. De Linares; J. Belmonte (International Journal of Biometeorology, 2022)

Long term forest management drives drought resilience in Mediterranean black pine forest - M. E. Lucas-Borja; E. Andivia; D. Candel-Pérez; J. C. Linares; J. J. Camarero (Trees, 2021)

Growth and resilience responses of Scots pine to extreme droughts across Europe depend on predrought growth conditions - Arun K. Bose; Arthur Gessler; Andreas Bolte; Alessandra Bottero; Allan Buras; Maxime Cailleret; J. Julio Camarero; Matthias Haeni; Ana‐Maria Hereş; Andrea Hevia; Mathieu Lévesque; Juan C. Linares; et al. (Global Change Biology, 2020)
Global climate change is expected to further raise the frequency and severity of extreme events, such as droughts. The effects of extreme droughts on trees are difficult to disentangle given the inherent complexity of drought events (frequency, severity, duration, and timing during the growing season). Besides, drought effects might be modulated by trees’ phenotypic variability, which is, in turn, affected by long‐term local selective pressures and management legacies. Here we investigated the magnitude and the temporal changes of tree‐level resilience (i.e., resistance, recovery, and resilience) to extreme droughts. Moreover, we assessed the tree‐, site‐, and drought‐related factors and their interactions driving the tree‐level resilience to extreme droughts. We used a tree‐ring network of the widely distributed Scots pine ( Pinus sylvestris ) along a 2,800 km latitudinal gradient from southern Spain to northern Germany. We found that the resilience to extreme drought decreased in mid‐elevation and low productivity sites from 1980–1999 to 2000–2011 likely due to more frequent and severe droughts in the later period. Our study showed that the impact of drought on tree‐level resilience was not dependent on its latitudinal location, but rather on the type of sites trees were growing at and on their growth performances (i.e., magnitude and variability of growth) during the predrought period. We found significant interactive effects between drought duration and tree growth prior to drought, suggesting that Scots pine trees with higher magnitude and variability of growth in the long term are more vulnerable to long and severe droughts. Moreover, our results indicate that Scots pine trees that experienced more frequent droughts over the long‐term were less resistant to extreme droughts. We, therefore, conclude that the physiological resilience to extreme droughts might be constrained by their growth prior to drought, and that more frequent and longer drought periods may overstrain their potential for acclimation.

Combining Isotopic Techniques to Assess Historical Sediment Delivery in a Forest Catchment in Central Chile - C. Bravo-Linares; P. Schuller; A. Castillo; A. Salinas-Curinao; L. Ovando-Fuentealba; E. Muñoz-Arcos; A. Swales; M. Gibbs; G. Dercon (Journal of Soil Science and Plant Nutrition, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Differences in the impact of heat waves according to urban and peri-urban factors in Madrid - J. A. López-Bueno; J. Díaz; C. Linares (International Journal of Biometeorology, 2019)

Wreckfish (Polyprion americanus). New Knowledge About Reproduction, Larval Husbandry, and Nutrition. Promise as a New Species for Aquaculture - Evaristo Pérez; Fátima Linares; José Luis Rodríguez Villanueva; Antonio Vilar; Constantinos C. Mylonas; Ioannis Fakriadis; Maria Papadaki; Nikos Papandroulakis; Ioannis Papadakis; Rocío Robles; Christian Fauvel; Javier Roo; et al. (Fishes, 2019)
Four different wreckfish (Polyprion americanus) broodstock batches were maintained in research facilities under different photo and thermo-period conditions, one in Greece, the Helenic Center for Marine Research (HCMR, n = 3) and three in Spain: Instituto Español de Oceanografía (IEO, n = 13) in Vigo, Aquarium Finisterrae (MC2, n = 21) in A Coruña and Consellería do Mar (CMRM, n = 11). The CMRM includes two centers that work together: Instituto Galego de Formación en Acuicultura (IGAFA) and Centro de Investigacións Mariñas (CIMA), both in Pontevedra. During the five years of the project DIVERSIFY (Exploring the biological and socio-economic potential of new-emerging candidate fish species for the expansion of the European aquaculture industry, 2013–2018) works focused on the reproductive biology of the species, broodstock, and larvae nutrition and development of incubation and larval rearing protocols have been carried out. In terms of reproduction, catch methods of new wild animals, the reproductive cycle, sperm characteristics evaluation, and spontaneous and induced spawning methods have been described for wreckfish. Regarding nutrition, the positive effect of two types of enrichment on the fatty acid profiles of Artemia and rotifer has been verified. The relationship between the fatty acid profile of the diets supplied to the broodstock and the fatty acid profile obtained in the oocytes and eggs of the females fed with different diets, has also been demonstrated. Finally, early larval ontogeny has been described and incubation and larval rearing protocols have been proposed based on the results obtained in the different experiments of temperature, growth, survival, and larval feeding that were carried out.

Description of the Annual Reproductive Cycle of Wreckfish Polyprion americanus in Captivity - Maria Papadaki; José Benito Peleteiro; Blanca Alvarez-Blázquez; José Luis Rodríguez Villanueva; Fatima Linares; Antonio Vilar; Evaristo Pérez Rial; Nuria Lluch; Ioannis Fakriadis; Irini Sigelaki; Constantinos C. Mylonas (Fishes, 2018)
Successful spontaneous reproduction and the production of viable offspring of wild fish in captivity can take some years of adaptation, and may also involve different environmental conditions, sex ratios and densities compared to natural populations. We followed the reproductive cycle of wreckfish Polyprion americanus—a late maturing, deep-sea benthic species—in captivity in three different broodstocks in Spain under natural photoperiod and temperature, and one broodstock in Greece under a constant temperature of 16 °C for two consecutive years, to describe the reproductive cycle of the species and the associated sex steroid hormone profiles. Oogenesis begun in the fall and post-vitellogenic oocytes of 1250 μm were present between March and June. Males were in spermiation condition and produced good-quality sperm throughout the year, regardless of the temperature profile to which they were exposed. Some females completed oogenesis, underwent oocyte maturation, and spawned spontaneously under both constant and fluctuating temperatures. The sex steroid hormones of both males and females followed the already-known profiles during fish gametogenesis, except for 17,20β-dihydroxy-progesterone, which did not seem to be related to either female or male maturation. The female reproductive dysfunctions that were identified included (a) the arrest of oogenesis at the cortical alveoli stage in certain females; (b) the failure to undergo oocyte maturation in others; and (c) the production of large percentages of unfertilized eggs from the females that spawned spontaneously. Our study suggests that reproduction in captivity is possible in wreckfish maintained under typical marine aquaculture conditions, but that reliable spawning and production of high-quality eggs may require some years of adaptation to captivity, before the reproductive dysfunctions will be overcome.

Abies pinsapo Boiss. Transcriptome Sequencing and Molecular Marker Detection: A Novel Genetic Resources for a Relict Mediterranean Fir - A Pérez-González; M Marconi; I Cobo-Simón; B Méndez-Cea; P Perdiguero; R Linacero; J C Linares; F J Gallego (Forest Science, 2018)

Resist, recover or both? Growth plasticity in response to drought is geographically structured and linked to intraspecific variability in Pinus pinaster - Raúl Sánchez‐Salguero; J. Julio Camarero; Vicente Rozas; Mar Génova; José M. Olano; Alberto Arzac; Antonio Gazol; Leocadia Caminero; Ernesto Tejedor; Martín de Luis; Juan C. Linares (Journal of Biogeography, 2018)
Aim We investigate the effects of the environmental and geographical processes driving growth resilience and recovery in response to drought in Mediterranean Pinus pinaster forests. We explicitly consider how intraspecific variability modulates growth resilience to drought. Location Western Mediterranean basin. Methods We analysed tree rings from a large network of 48 forests (836 trees) encompassing wide ecological and climatic gradients, including six provenances. To characterize the major constraints of P. pinaster growth under extremely dry conditions, we simulated growth responses to temperature and soil moisture using a process‐based growth model coupled with the quantification of climate–growth relationships. Then, we related growth–resilience indices to provenance and site variables considering different drought events. Results Pinus pinaster displayed strong variation in growth resilience across its distributional range, but common patterns were found within each provenance. Post‐drought resilience increased with elevation and drier conditions but decreased with spring precipitation. Trees from dry sites were less resistant to drought but recovered faster than trees from wet sites. Main conclusions Resilience strategies differed among tree provenances: wet forests showed higher growth resistance to drought, while dry forests presented faster growth recovery, suggesting different impacts of climate warming on forest productivity. We detected geographically structured resilience patterns corresponding to different provenances, confirming high intraspecific variability in response to drought. This information should be included in species distribution models to simulate forest responses to climate warming and forecasted aridification.

Forest resilience to drought varies across biomes - Antonio Gazol; Jesus Julio Camarero; Sergio M. Vicente‐Serrano; Raúl Sánchez‐Salguero; Emilia Gutiérrez; Martin de Luis; Gabriel Sangüesa‐Barreda; Klemen Novak; Vicente Rozas; Pedro A. Tíscar; Juan C. Linares; Natalia Martín‐Hernández; et al. (Global Change Biology, 2018)
Forecasted increase drought frequency and severity may drive worldwide declines in forest productivity. Species‐level responses to a drier world are likely to be influenced by their functional traits. Here, we analyse forest resilience to drought using an extensive network of tree‐ring width data and satellite imagery. We compiled proxies of forest growth and productivity ( TRW i, absolutely dated ring‐width indices; NDVI , Normalized Difference Vegetation Index) for 11 tree species and 502 forests in Spain corresponding to Mediterranean, temperate, and continental biomes. Four different components of forest resilience to drought were calculated based on TRW i and NDVI data before, during, and after four major droughts (1986, 1994–1995, 1999, and 2005), and pointed out that TRW i data were more sensitive metrics of forest resilience to drought than NDVI data. Resilience was related to both drought severity and forest composition. Evergreen gymnosperms dominating semi‐arid Mediterranean forests showed the lowest resistance to drought, but higher recovery than deciduous angiosperms dominating humid temperate forests. Moreover, semi‐arid gymnosperm forests presented a negative temporal trend in the resistance to drought, but this pattern was absent in continental and temperate forests. Although gymnosperms in dry Mediterranean forests showed a faster recovery after drought, their recovery potential could be constrained if droughts become more frequent. Conversely, angiosperms and gymnosperms inhabiting temperate and continental sites might have problems to recover after more intense droughts since they resist drought but are less able to recover afterwards.

Contrasting growth forecasts across the geographical range of Scots pine due to altitudinal and latitudinal differences in climatic sensitivity - Luis Matías; Juan C. Linares; Ángela Sánchez‐Miranda; Alistair S. Jump (Global Change Biology, 2017)
Ongoing changes in global climate are altering ecological conditions for many species. The consequences of such changes are typically most evident at the edge of a species’ geographical distribution, where differences in growth or population dynamics may result in range expansions or contractions. Understanding population responses to different climatic drivers along wide latitudinal and altitudinal gradients is necessary in order to gain a better understanding of plant responses to ongoing increases in global temperature and drought severity. We selected Scots pine ( Pinus sylvestris L.) as a model species to explore growth responses to climatic variability (seasonal temperature and precipitation) over the last century through dendrochronological methods. We developed linear models based on age, climate and previous growth to forecast growth trends up to year 2100 using climatic predictions. Populations were located at the treeline across a latitudinal gradient covering the northern, central and southernmost populations and across an altitudinal gradient at the southern edge of the distribution (treeline, medium and lower elevations). Radial growth was maximal at medium altitude and treeline of the southernmost populations. Temperature was the main factor controlling growth variability along the gradients, although the timing and strength of climatic variables affecting growth shifted with latitude and altitude. Predictive models forecast a general increase in Scots pine growth at treeline across the latitudinal distribution, with southern populations increasing growth up to year 2050, when it stabilizes. The highest responsiveness appeared at central latitude, and moderate growth increase is projected at the northern limit. Contrastingly, the model forecasted growth declines at lowland‐southern populations, suggesting an upslope range displacement over the coming decades. Our results give insight into the geographical responses of tree species to climate change and demonstrate the importance of incorporating biogeographical variability into predictive models for an accurate prediction of species dynamics as climate changes.

Across-scale patterning of plant–soil–pathogen interactions in Quercus suber decline - J. M. Avila; J. C. Linares; A. García-Nogales; M. E. Sánchez; L. Gómez-Aparicio (European Journal of Forest Research, 2017)

A synthesis of radial growth patterns preceding tree mortality - Maxime Cailleret; Steven Jansen; Elisabeth M. R. Robert; Lucía Desoto; Tuomas Aakala; Joseph A. Antos; Barbara Beikircher; Christof Bigler; Harald Bugmann; Marco Caccianiga; Vojtěch Čada; Jesus J. Camarero; et al. (Global Change Biology, 2017)
Tree mortality is a key factor influencing forest functions and dynamics, but our understanding of the mechanisms leading to mortality and the associated changes in tree growth rates are still limited. We compiled a new pan‐continental tree‐ring width database from sites where both dead and living trees were sampled (2970 dead and 4224 living trees from 190 sites, including 36 species), and compared early and recent growth rates between trees that died and those that survived a given mortality event. We observed a decrease in radial growth before death in ca. 84% of the mortality events. The extent and duration of these reductions were highly variable (1–100 years in 96% of events) due to the complex interactions among study species and the source(s) of mortality. Strong and long‐lasting declines were found for gymnosperms, shade‐ and drought‐tolerant species, and trees that died from competition. Angiosperms and trees that died due to biotic attacks (especially bark‐beetles) typically showed relatively small and short‐term growth reductions. Our analysis did not highlight any universal trade‐off between early growth and tree longevity within a species, although this result may also reflect high variability in sampling design among sites. The intersite and interspecific variability in growth patterns before mortality provides valuable information on the nature of the mortality process, which is consistent with our understanding of the physiological mechanisms leading to mortality. Abrupt changes in growth immediately before death can be associated with generalized hydraulic failure and/or bark‐beetle attack, while long‐term decrease in growth may be associated with a gradual decline in hydraulic performance coupled with depletion in carbon reserves. Our results imply that growth‐based mortality algorithms may be a powerful tool for predicting gymnosperm mortality induced by chronic stress, but not necessarily so for angiosperms and in case of intense drought or bark‐beetle outbreaks.

Plant maintenance and environmental stress. Summarising the effects of contrasting elevation, soil, and latitude on Quercus ilex respiration rates - Raquel G. Laureano; Ana García-Nogales; José I. Seco; Juan C. Linares; Feliciano Martínez; José Merino (Plant and Soil, 2016)

Range‐wide variation in life‐history phenotypes: spatiotemporal plasticity across the latitudinal gradient of the evergreen oak Quercus ilex - Ana García‐Nogales; Juan C. Linares; Raquel G. Laureano; Jose I. Seco; Jose Merino (Journal of Biogeography, 2016)
Aim Stressful environments, like those at the limits of species ranges, are closely associated with the selective establishment of particular traits, yet the mechanisms behind this relationship are poorly understood. Our main aim was to investigate spatial and temporal phenotypic plasticity related to environmental conditions and biogeographical origin. Location A latitudinal gradient along Iberian Peninsula and Morocco, western Mediterranean Basin. Methods We investigate the intra‐specific variability in the Mediterranean oak Quercus ilex subsp. ballota , covering most of its latitudinal range. Acorns were collected in the years 2009, 2011, 2012 and 2013 from natural populations and were grown under controlled conditions. We measured acorn mass and germination dynamics, as well as seedling morphology. Results Field data showed significant differences in stand structure among populations. The southernmost population presented the smallest trees, followed by the northernmost population. Core‐range trees registered higher values for leaf‐nitrogen concentration. Leaf size showed latitudinal variation, with the lowest values at the northern range limit. In addition, the germination pattern also significantly differed among populations, showing a latitudinal pattern of variation (i.e. the southern populations germinated earlier). Fresh acorn mass showed significant within‐ and among‐population differences, displaying a range margin pattern (i.e. similarities between the edge populations). Furthermore, seedling total weight and biomass allocation also followed the same pattern. The models explaining the most part of the trait variance were related mainly to climatic variables (reflecting temporal variability), while the random effect of the models (population) showed a range margin pattern with lower values in edge populations compared with core populations. Main conclusions Similar phenotypic traits among individuals native to the periphery of the distribution range were found despite the temporal variability, suggesting adaptation to stressful environments at the range edges.

Adhesio interthalamica and cavum septum pellucidum in mesial temporal lobe epilepsy - Clarissa Trzesniak; Ila M. Linares; Érica R. Coimbra; Alexandre Veriano Júnior; Tonicarlo R. Velasco; Antonio C. Santos; Jaime E. Hallak; Americo C. Sakamoto; Geraldo F. Busatto; José A. Crippa (Brain Imaging and Behavior, 2016)

Time trend in natural-cause, circulatory-cause and respiratory-cause mortality associated with cold waves in Spain, 1975–2008 - C. Linares; I. J. Mirón; R. Carmona; R. Sánchez; J. Díaz (Stochastic Environmental Research and Risk Assessment, 2016)

Microbial stress priming: a meta‐analysis - Diana R. Andrade‐Linares; Anika Lehmann; Matthias C. Rillig (Environmental Microbiology, 2016)
Summary Microbes have to cope with complex and dynamic environments, making it likely that anticipatory responses provide fitness benefits. Mild, previous stressors can prepare microbes (stress priming) to further and potentially damaging stressors (triggering). We here quantitatively summarize the findings from over 250 trials of 34 studies including bacteria and fungi, demonstrating that priming to stress has a beneficial impact on microbial survival. In fact, survival of primed microbes was about 10‐fold higher compared with that in non‐primed microbes. Categorical moderators related to microbial taxonomy and the kind of stress applied as priming or as triggering revealed significant differences of priming effect size among 14 different microbial species, 6 stress categories and stressor combination. We found that priming by osmotic, physiological and temperature stress had the highest positive effect sizes on microbial response. Cross‐protection was evident for physiological, temperature and pH stresses. Microbes are better prepared against triggering by oxidative, temperature and osmotic stress. Our finding of an overall positive mean effect of priming regardless of the microbial system and particular stressor provides unprecedentedly strong evidence of the broad ecological significance of microbial stress priming. These results further suggest that stress priming may be an important factor in shaping microbial communities.

The effect of climate-change-related heat waves on mortality in Spain: uncertainties in health on a local scale - E. Roldán; M. Gómez; M. R. Pino; J. Pórtoles; C. Linares; Julio Díaz (Stochastic Environmental Research and Risk Assessment, 2016)

Alternaria spores in the air across Europe: abundance, seasonality and relationships with climate, meteorology and local environment - C. A. Skjøth; A. Damialis; J. Belmonte; C. De Linares; S. Fernández-Rodríguez; A. Grinn-Gofroń; M. Jędryczka; I. Kasprzyk; D. Magyar; D. Myszkowska; G. Oliver; A. Páldy; et al. (Aerobiologia, 2016)

Impact of heat and cold waves on circulatory-cause and respiratory-cause mortality in Spain: 1975–2008 - C. Linares; J. Diaz; A. Tobías; R. Carmona; I. J. Mirón (Stochastic Environmental Research and Risk Assessment, 2015)

Recruitment patterns in the Mediterranean deep-water alga Cystoseira zosteroides - P. Capdevila; C. Linares; E. Aspillaga; L. Navarro; D. K. Kersting; B. Hereu (Marine Biology, 2015)

Influence of advections of particulate matter from biomass combustion on specific-cause mortality in Madrid in the period 2004–2009 - C. Linares; R. Carmona; A. Tobías; I. J. Mirón; J. Díaz (Environmental Science and Pollution Research, 2015)

Predicting climate change impacts on native and invasive tree species using radial growth and twenty-first century climate scenarios - N. González-Muñoz; J. C. Linares; P. Castro-Díez; U. Sass-Klaassen (European Journal of Forest Research, 2014)

Integrated geophysical and morphostratigraphic approach to investigate a coseismic (?) translational slide responsible for the destruction of the Montclús village (Spanish Pyrenees) - M. Zarroca; R. Linares; C. Roqué; J. Rosell; F. Gutiérrez (Landslides, 2014)

Comparative pharmacokinetics of PAMAM-OH dendrimers and HPMA copolymers in ovarian tumor-bearing mice - S. Sadekar; O. Linares; G. J. Noh; D. Hubbard; A. Ray; M. Janát-Amsbury; C. M. Peterson; J. Facelli; H. Ghandehari (Drug Delivery and Translational Research, 2013)

Growth and maintenance costs of leaves and roots in two populations of Quercus ilex native to distinct substrates - Raquel G. Laureano; Ana García-Nogales; José I. Seco; Jesús G. P. Rodríguez; Juan C. Linares; Feliciano Martínez; José Merino (Plant and Soil, 2013)

Safety analysis of high dose (>6 mg/kg/day) daptomycin in patients with concomitant statin therapy - J. Parra-Ruiz; C. Dueñas-Gutiérrez; C. Tomás-Jiménez; J. P. Linares-Palomino; J. Garrido-Gomez; J. Hernández-Quero (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Assessment of cattle welfare at a commercial slaughter plant in the northwest of Mexico - Genaro C. Miranda-de la Lama; Iván G. Leyva; Alberto Barreras-Serrano; Cristina Pérez-Linares; Eduardo Sánchez-López; Gustavo A. María; Fernando Figueroa-Saavedra (Tropical Animal Health and Production, 2012)

Human impacts drive forest structure and diversity. Insights from Mediterranean mountain forest dominated by Abies pinsapo (Boiss.) - J. C. Linares; J. A. Carreira; V. Ochoa (European Journal of Forest Research, 2011)

African ancestry is associated with risk of asthma and high total serum IgE in a population from the Caribbean Coast of Colombia - Candelaria Vergara; Luis Caraballo; Dilia Mercado; Silvia Jimenez; Winston Rojas; Nicholas Rafaels; Tracey Hand; Monica Campbell; Yuhjung J. Tsai; Li Gao; Constanza Duque; Sergio Lopez; et al. (Human Genetics, 2009)

Mass mortality in Northwestern Mediterranean rocky benthic communities: effects of the 2003 heat wave - J. GARRABOU; R. COMA; N. BENSOUSSAN; M. BALLY; P. CHEVALDONNÉ; M. CIGLIANO; D. DIAZ; J. G. HARMELIN; M. C. GAMBI; D. K. KERSTING; J. B. LEDOUX; C. LEJEUSNE; et al. (Global Change Biology, 2009)
Late in summer 2003, extensive mass mortality of at least 25 rocky benthic macro‐invertebrate species (mainly gorgonians and sponges) was observed in the entire Northwestern (NW) Mediterranean region, affecting several thousand kilometers of coastline. We were able to characterize the mortality event by studying six areas covering the main regions of the NW Mediterranean basin. The degree of impact on each study area was quantified at 49 sites by estimating the proportion of colonies affected in populations of several gorgonian species compared with reference data obtained in years without mortality signs. According to these data, the western areas (Catalan coast and Balearic Islands) were the least affected, while the central areas (Provence coast and Corsica‐Sardinia) showed a moderate impact. The northernmost and eastern areas (Gulf of Genoa and Gulf of Naples) displayed the highest impact, with almost 80% of gorgonian colonies affected. The heat wave of 2003 in Europe caused an anomalous warming of seawater, which reached the highest temperatures ever recorded in the studied regions, between 1 and 3 °C above the climatic values (mean and maximum). Because this exceptional warming was observed in the depth ranges most affected by the mortality, it seems likely that the 2003 anomalous temperature played a key role in the observed mortality event. A correlation analysis between temperature conditions and degree of impact seems to support this hypothesis. Under the present climate warming trend, new mass mortality events may occur in the near future, possibly driving a major biodiversity crisis in the Mediterranean Sea.

Mass mortality in NW Mediterranean rocky benthic communities: effects of the 2003 heat wave - J. GARRABOU; R. COMA; N. BENSOUSSAN; M. BALLY; P. CHEVALDONNÉ; M. CIGLIANO; D. DIAZ; J. G. HARMELIN; M. C. GAMBI; D. K. KERSTING; J. B. LEDOUX; C. LEJEUSNE; et al. (Global Change Biology, 2008)

Effects of a mass mortality event on gorgonian reproduction - C. Linares; R. Coma; M. Zabala (Coral Reefs, 2008)

Cinnamtannin B-1 from bay wood exhibits antiapoptotic effects in human platelets - A. Bouaziz; C. Romera-Castillo; S. Salido; P. J. Linares-Palomino; J. Altarejos; A. Bartegi; J. A. Rosado; G. M. Salido (Apoptosis, 2007)

Comparative effects of melatonin and vitamin E in restoring aortic relaxation in pancreatectomized rats - C. F. Reyes-Toso; L. M. Linares; L. E. Albornoz; D. Obaya-Naredo; M. L. Wallinger; C. R. Ricci; D. P. Cardinali (Journal of Physiology and Biochemistry, 2006)

Airborne-pollen map for Olea europaea L. in eastern Andalusia (Spain) using GIS: Estimation models - F. Alba; D. Nieto-Lugilde; P. Comtois; C. Díaz de la Guardia; C. De Linares; L. Ruiz (Aerobiologia, 2006)

Impact of urban air pollutants and noise levels over daily hospital admissions in children in Madrid: a time series analysis - C. Linares; J. Díaz; A. Tobías; J. M. De. Miguel; A. Otero (International Archives of Occupational and Environmental Health, 2006)

The impact of the summer 2003 heat wave in Iberia: how should we measure it? - J. Díaz; R. García-Herrera; R. M. Trigo; C. Linares; M. A. Valente; J. M. De Miguel; E. Hernández (International Journal of Biometeorology, 2006)

A Computer Reconstruction of the Entire Coronary Arterial Tree Based on Detailed Morphometric Data - N. Mittal; Y. Zhou; S. Ung; C. Linares; S. Molloi; G. S. Kassab (Annals of Biomedical Engineering, 2005)

Mortality impact of extreme winter temperatures - Julio Daz; Ricardo Garca; Csar Lpez; Cristina Linares; Aurelio Tobas; Luis Prieto (International Journal of Biometeorology, 2005)

Temporal and spatial variability in settlement of the sea urchin Paracentrotus lividus in the NW Mediterranean - B. Hereu; M. Zabala; C. Linares; E. Sala (Marine Biology, 2004)

Discrimination of the closely related A and B genomes in AABB tetraploid species of Avena - M. L. Irigoyen; Y. Loarce; C. Linares; E. Ferrer; M. Leggett; A. Fominaya (Theoretical and Applied Genetics, 2001)

Identification of C-genome chromosomes involved in intergenomic translocations in Avena sativa L., using cloned repetitive DNA sequences - C. Linares; M. L. Irigoyen; A. Fominaya (Theoretical and Applied Genetics, 2000)

Detection of a cell-cycle inhibitor of Petunia hybrida protoplasts in an Arthrospira platensis extract - Michel C. Hours; Peggy N. Linares; Thi Hai Phan; Rémy Filali-Mouhim (Biotechnology Letters, 1998)

Appearance of Colonies of Prototheca on CHROMagar Candida medium - Manuel Casal; María José Linares; Francisco Solís; Fernando C. Rodríguez (Mycopathologia, 1997)

Study of onychomycosis in Córdoba, Spain: Prevailing fungi and pattern of infection - Antonio Vélez; Ma José Linares; José C. Fenández-Roldán; Manuel Casal (Mycopathologia, 1997)